2015
DOI: 10.1080/14783363.2015.1064767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sustainability-oriented innovation practices on the overall organisational performance: an empirical examination

Abstract: One major means to address corporate sustainability practices in organizations are sustainability-oriented innovation practices, which tend to result in significantly improved products, services, processes or even management systems. Prior research has widely discussed the relevant issues about integrating sustainability aspects into innovation process; however, little empirical research has been conducted to analyse the link between sustainability-oriented innovation practices and the overall organizational p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 70 publications
8
71
0
7
Order By: Relevance
“…To address the conflict between firm development and environmental protection, proposed the theoretical frameworks of SEXPLOR and SEXPLOI based on the prior "exploration-exploitation" paradigm and sustainable development theory [40]. SEXPLOR focuses on reducing both environmental costs and material consumption over the life of product through enhancing exploratory innovation, aiming to achieve firms' sustainability and obtain future prosperity in competitive edges [40].…”
Section: Sustainability Exploration Innovation and Sustainability Expmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the conflict between firm development and environmental protection, proposed the theoretical frameworks of SEXPLOR and SEXPLOI based on the prior "exploration-exploitation" paradigm and sustainable development theory [40]. SEXPLOR focuses on reducing both environmental costs and material consumption over the life of product through enhancing exploratory innovation, aiming to achieve firms' sustainability and obtain future prosperity in competitive edges [40].…”
Section: Sustainability Exploration Innovation and Sustainability Expmentioning
confidence: 99%
“…To address the conflict between firm development and environmental protection, proposed the theoretical frameworks of SEXPLOR and SEXPLOI based on the prior "exploration-exploitation" paradigm and sustainable development theory [40]. SEXPLOR focuses on reducing both environmental costs and material consumption over the life of product through enhancing exploratory innovation, aiming to achieve firms' sustainability and obtain future prosperity in competitive edges [40]. SEXPLOI, meanwhile, emphasizes the reduction of the use of materials, water, and energy with continuously improving production efficiency through enhancing exploitation innovation; this aims to contribute to existing competitive edges in the short-term [39].…”
Section: Sustainability Exploration Innovation and Sustainability Expmentioning
confidence: 99%
“…More recent studies that found positive relationship between EP and FP include Tarus (2015) for Kenya, Lin et al (2009) for Taiwan, Mishra and Suar (2010) for India, Hossain et al (2015) for Bangladesh, Lisi (2015) for Italy, and Maletič et al (2015) for multiple European countries (Germany, Poland, Serbia, Slovenia, and Spain). Hafez (2015) has found a weak positive (also neutral) link for the case of Egyptian banks, while Kamatra and Kartikaningdyah (2015) found a weak positive link for the case of Indonesian mining industry.…”
Section: Background and Theory On Environmental Performance-firm Perfmentioning
confidence: 99%
“…These questions were adapted from validated scales developed by Bharthvajan (2014), McAfee, Glassman and Honeycutt (2002), Choi and Harley (1996), Lee, Lee and Pennings (2001), Grover, Chopra and Mosher (2016), Thakur andHurburgh (2009), Bonner andCalantone (2005), Tsoulfas and Pappis (2006) and Steyn et al (2012). Section C measured business performance by using five questionnaire items adapted from studies by Brik, Rettab and Mellahi (2011) and Maletic et al (2015). The process of adapting these questions involved minor adjustments to the phrasing of the questions, their length and Likert-type scale configuration, in line with the recommendations by Sullivan (2011).…”
Section: Data Collection Methods and Proceduresmentioning
confidence: 99%